Ontogenetic morphogenesis and biogeographic patterns: Resolving taxonomic incongruences within "species" of Buccella from South American coastal waters - Calvo Marcilese, María Lydia Valentina (2012)
The analysis of ubiquitous material of individual growth stages of the foraminifer Buccella from the Bahía Blanca estuary reveals a wide range of morphogenetic expressions. The observations of morphological changes expressed during ontogeny display a continuous record of transitional stages that are reflected in juvenile, adolescent, and adult test shapes. The morphological features of individual growth stages were found to match specifications that were previously used to delineate individual species of Buccella from around South America. This indicates that juvenile, adolescent, and adult morphotypes of Buccella do not represent end members of individual species, subspecies, forms, or varieties. In fact, they constitute a continuous sequence of ontogenetic stages that ultimately result in the morphotype that was originally described and depicted by d'Orbigny, in the first half of the nineteenth century, under the name Rotalina peruviana (currently known as Buccella peruviana). The morphological expressions of juvenile, adolescent, and adult forms have potential applications for paleoecological studies in South American waters.